Kinetics of Lymphocytes Reconstitution Post Allogeneic Hematopoietic Stem Cell Transplantation: Two years of Follow-up - Eida Elmansorry, (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Allogeneic hematopoietic stem cells transplantation (HSCT) is strong curative treatment for several classes of immunodeficiency, metabolic disorders, and haematopoietic malignancies. Depending on HSCT procedure, thousands of patients could heal from their underlying disease. The ability of hematopoietic stem cells transplantation (HSCT) to cure is affected by variant factors. The objectives of this study were to analyze the kinetics of lymphocyte recovery at different time points after allogeneic hematopoietic stem cells transplantation and to correlate their recovery with some factors that influence the transplantation clinical outcome. Methods. In this study, 16 consecutive allogeneic hematopoietic stem cell transplantation (HSCT) recipients were analysed during the first two-year post transplantation by measuring the absolute count of lymphocytes every three months for each patient. Data were presented as minimum, maximum and mean. Results. Frequencies of lymphocytes increased gradually during the first 24 months post HSCT and their recovery was affected by different factors such as graft source, patient age, and chronic graft versus host disease. Lymphocytes are essential for adaptive immune responses. Type of transplant, graft versus host disease, and recipient age affect their reconstitution. Conclusion. Proper lymphocyte recovery is associated with better clinical outcome and increased the survival rate.